Writing Deconstructivist Architecture - Al-Asadi, Dr. Asaad Ghalib (Basrah Journal for Engineering Sciences, 2015)
Architecture is writing, based on the understanding that writing is a disturbance of a creative medium and a stirring of its waters. In a practice where its deconstructive text reshapes its systems by breaking traditions and exploring formations that contradict reality, rearranging it according to a new image. It involves selecting specific data from among options that displace the form from its traditional compliance with function, towards producing architectural spaces occupied with developing their formal discourse, and then calling for their employment in forms that give their users feelings creating an experience and presenting an idea with a boldness of creation not approached by creativity before. The architectural form is disturbed, dispersed, and twisted, confusing our familiar image of buildings and presenting other faces, confirming architecture's ability to renew its creative discourse, differing from what is expected of it, enriching our visual experience with other experiments, renewing the vitality of reception, and sustaining the phenomenon of architecture's survival, as in the works of Daniel Libeskind, Zaha Hadid, Peter Eisenman, Frank Gehry, and Bernard Tschumi.